Термиз шаҳри туристик салоҳияти (SCIENCE and SOCIETY, 2023)
This article describes some of the memorial and archaeological monuments of the city of Termez and the geography of cultural heritage sites, as well as the current state of the tourist infrastructure of the city, which are the basis for the development of tour- ism in the city of Termez.